#TITLE_ALTERNATIVE# - ASSIFA (NIM : 12910022), FUAD
Hot water waste from Steam Generated Power Plant (PLTU) was hotter than the temperature of surrounding water. The massive influx of hot water waste from PLTU outlet into the ocean could yield into a negative impact toward the marine biota in the region. To study the scattered pattern and quantity of change of the temperature difference due to hot water waste, this study used 2 dimension (2D) horizontal hydrodynamic model and temperature transport model from MIKE 21. The data used in the simulation were tidal data, wind data, bathymetry, coastline data, inlet and outlet discharge, normal sea water temperature, and water temperature from outlet. Model scenario conducted during west monsoon and east monsoon. The result of the simulation showed during flood tide, sea water had higher temperature from outlet and spread toward west of outlet while on ebb tide it spread to east of outlet. The area which had ΔT above 2 Ã‚Â°C during the east monsoon was 1.014.750 m2 and was bigger than area covered during the west monsoon with 963.494 m2 area coverage. Maximum raised in temperature in inlet happened during the maximum flood tide during the east monsoon with ΔT 4 Ã‚Â°C.